Comprehensive proteomic atlas of skin biomatrix scaffolds reveals a supportive microenvironment for epidermal development. (November 2020) - Leng, Ling; Ma, Jie; Sun, Xuer; Guo, Baolin; Li, Fanlu; Zhang, Wei; Chang, Mingyang; Diao, Jinmei; Wang, Yi; Wang, Wenjuan; Wang, Shuyong; Zhu, Yunping; et al.
Biomaterial scaffolds are increasingly being used to drive tissue regeneration. The limited success so far in human tissues rebuilding and therapy application may be due to inadequacy of the functionality biomaterial scaffold. We developed a new decellularized method to obtain complete anatomical skin biomatrix scaffold in situ with extracellular matrix (ECM) architecture preserved, in this study. We described a skin scaffold map by integrated proteomics and systematically analyzed the interaction between ECM proteins and epidermal cells in skin microenvironment on this basis. They were used to quantify structure and function of the skin's Matrisome, comprised of core ECM components and ECM-associated soluble signals that are key regulators of epidermal development. We especially revealed that ECM played a role in determining the fate of epidermal stem cells through hemidesmosome components. These concepts not only bring us a new understanding of the role of the skin ECM niche, they also provide an attractive combinational strategy based on tissue engineering principles with skin biomatrix scaffold materials for the acceleration and enhancement of tissue regeneration.